(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article clarifies the concept of “teaching technology” as applied to foreign-language (English) education. It traces the emergence of educational technology in the mid-twentieth century from behaviourist psychology, Bloom’s taxonomy of objectives, and the systems approach to instructional design, and distinguishes the term’s two principal readings – the technical means of instruction and the systematic, reproducible design of the teaching process. Drawing on the Russian-language tradition of “pedagogical technology” (Bespalko, Selevko) and on the methodological framework of applied linguistics (Anthony’s approach–method–technique), it relates the category of “method” to that of “teaching technology,” surveys the principal families of instructional design (communicative, task-based, project-based, cooperative, game- and computer assisted), and sets out the criteria for selecting a technology in the conditions of Uzbekistan, including alignment with the Common European Framework of Reference for Languages and with learners’ age. The article concludes by defining the technology of teaching English as a scientifically grounded, procedurally organised, and reproducible system for designing, conducting, and evaluating the teaching process